Prenatal onset of the neuroradiologic phenotype of pyruvate carboxylase deficiency due to homozygous PC c.1828G > A mutations. Issue 1 (14th June 2021) - Mhanni, Aizeddin A.; Rockman‐Greenberg, Cheryl; Ryner, Lawrence; Bunge, Martin
Abstract: Pyruvate carboxylase (PC) deficiency (MIM# 266150) is an autosomal recessive disorder with three subtypes. Patients homozygous for the c.1828G > A mutation in the PC gene belong to type A, which typically has infantile onset, severe to profound developmental delay, hypotonia, and lactic acidemia. We report the neuroimaging abnormalities in a 33‐week gestation infant homozygous for the c.1828G > A mutation. Brain magnetic resonance imaging on day 10 of life revealed increased T2 signal within the subcortical and periventricular white matter, an immature gyral pattern, large periventricular cysts with mass effect on the lateral ventricles, and dilatation of the occipital and temporal horns. Magnetic resonance spectroscopy showed reduced creatine and NAA peaks, a relatively high choline peak and no lactate peak. These findings were observed prior to the neonate experiencing any episodes of decompensation with lactic acidosis. The presence of these brain anomalies at this gestational age, prior to any metabolic decompensation, supports the essential role of PC in normal brain morphogenesis and the resulting in‐utero brain anomalies secondary to its deficiency. Our experience with this affected premature infant and many others we have managed with the same founder mutation suggests that the clinical phenotypes of the type A and the more severe type B PC deficient patients are on a spectrum rather than distinct subtypes.